The Man Without a Face: The Unlikely Rise of Vladimir Putin (Trans-pasando Fronteras, 2013)
Bibliographic outline of the following book:GESSEN, Masha (2012). The Man Without a Face-The Unlikely Rise of Vladimir Putin. Riverhead Books, 322 pp.